ANALISIS POLA PERGERAKAN DI KOTA DENPASAR - Suthanaya, Putu Alit; Maulidawati, Candra (Jurnal Ilmiah Teknik Sipil, 2019)
The city of Denpasar has been developed from a small city, a large city and then formed a metropolitan city with the surrounding regions. To anticipate the need of transport infrastructure in the future, it is required to study the travel pattern. In this research two transportation models were developed, i.e. trip distribution and trip assignment. the aim of this research is to predict the trip distribution and traffic load in Denpasar City's road network in the future and also to compare the trip distribution. The modeling in this research were made with Visum software version 15. The methods applied for trip distribution model was doubly constrainted method and trip assignment was based on equilibrium assignment method. It was predicted that the total trip distribution for Denpasar City in year 2033 are 28.873.490 persons/day (308.845.109 person-kms). The highest traffic load was found in Jl. By Pass Ngurah Rai. Its is required to build new road links or applying demand management by prioritising public transport and reduce the use of private motor vehicles.